EVALUASI TAHAPAN INTERVENSI SOSIAL PADA KELOMPOK NELAYAN DALAM PROGRAM PENGEMBANGAN PERIKANAN TANGKAP DI DUKUH TAMBAKREJO KOTA SEMARANG - Raharjo, Senoaji Yuda; Djumiarti, Titik (Journal of Public Policy and Management Review, 2017)
This research is aimed to identify the shape of a given social interventions and evaluate the stages of social intervention in order to obtain good performance of program and to identify whether there is result of the implementation of social interventions provided by Department of Marine Affairs and Fisheries Semarang through Fisheries Development Program in Tambakrejo Hamlet, Semarang. This research is a qualitative descriptive study with data collection through interviews and documentation. Informants were selected by researcher is employees of Department of Marine Affairs and Fisheries Semarang and fishermen communities in Tambakrejo Hamlet, Semarang. In this study, researcher used a phase of social interventions to see if the social intervention provided is in accordance with the stages of implementation and use phases of policy evaluation. The results showed that social interventions provided by Department of Marine Affairs and Fisheries Semarang has been running well and in conformity with the implementation phase. Results of the administration of the social intervention is fishermen awareness to use environmental friendly fishing gear, fishermen awareness of safety at sea, fishermen skill enhancement, and increasing fish catches. But the intervention provided also still has shortcomings, that is in terms of the implementation stages, the data collection phase, the contract negotiation phase, and termination phase. Termination stage or termination of intervention activities can not be done, it is because a given social intervention has not been fully able to resolve all problems in Tambakrejo Hamlet, Semarang. Furthermore, supervision and sanctions toward fishermen who still use dangerous fishing gear has not given explicitly. Social interventions is still not fully utilized by some fishermen. The advices can be given by researcher is to raise awareness to protect the environment, involving collaboration with the private sector, eliminating the lazy attitude of fishermen, apply strict supervision and sanctions to fishermen who commit violation. While the advice can be given to other researchers that will research the social intervention in order to pay attention to the excavation problems stage and establishing a system of action. Due to give an intervention need to be excavated and the main problems involve other parties for the implementation of a given intervention can run well.